Peran Mikroorganisme Dalam Meningkatkan Kualitas Tanah Dan Toleransi Tanaman Terhadap Cekaman Abiotik - Zendrato, Intan Novibriani; Lase, Natalia Kristiani (CV. SINAR HOWUHOWU, 2024)
Soil microbiota play an important role in improving soil quality and supporting plant tolerance to abiotic stresses such as drought, salinity, extreme temperatures and pollution. Soil microorganisms, such as bacteria, fungi and microalgae, are involved in various processes that support plant growth and improve soil structure and fertility. Microbial activities such as nitrogen fixation, decomposition of organic matter, breakdown of toxic compounds, and formation of biofilms that protect plants from pathogens and harmful environmental factors are important in enhancing plant resilience. In addition, microorganisms also help increase nutrient availability and regulate soil pH. This can affect the ability of plants to survive under abiotic stress conditions. This article reviews the various mechanisms by which soil microorganisms enhance stress tolerance in plants and their potential application as biotechnological agents for sustainable agriculture to address the challenges of climate change.